Pengaruh Cybersecurity Disclosure dan Financial Flexibility terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening pada PT Telkom Indonesia Tbk Periode 2015–2024 - Yunus Nurhasan; Sri Mardiana (Journal Economic Management and Business, 2026)
This study examines the effect of cybersecurity disclosure and financial flexibility on firm value with profitability as an intervening variable at PT Telkom Indonesia Tbk for the period 2015–2024. Using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0, this study analyzes annual report data and financial statements over ten years. The outer model evaluation confirms satisfactory validity (AVE > 0.50) and reliability (CR > 0.70) for all constructs. The inner model results show that cybersecurity disclosure positively and significantly affects profitability (β = 0.412, t = 3.871) and firm value (β = 0.389, t = 3.652). Financial flexibility also positively affects profitability (β = 0.358, t = 3.214) and firm value (β = 0.271, t = 2.540). Profitability partially mediates both relationships. The model explains 58.1% variance in profitability and 67.3% in firm value. These findings confirm that transparency in cybersecurity risk management and financial buffer capacity are key determinants of investor confidence and firm value in the digital transformation era